Scarification, temperature and light in germination of Senna occidentalis seed (Caesalpinaceae) - Delachiave, M. E.A. [UNESP]; De Pinho, S. Z. [UNESP] (International Seed Testing Association, 2003)
The purpose of the present work was to study various aspects of the germination of seeds of Senna occidentalis Link, which had presented promising results in biological activity against the etiological agent of malaria. These aspects were dormancy, temperatures of germination and photoblastic response. In the dormancy studies, the treatments used were: unscarified seed (control); tegument puncture with sharp point; and scarification with sand-paper and immersion in concentrated sulfuric acid during 5, 10, 15 and 20 minutes. For the study of temperature and photoblast, the seeds were immersed in sulfuric acid for 20 minutes, submitted to temperatures of 10 to 45°C, at intervals of 5°C, both under light and in the dark. The seeds presented dormancy related to tegument, the best treatments for breaking dormancy were immersion in sulfuric acid for 15 and 20 minutes. At temperatures 25 and 30°C, the best results of percentage and index of velocity of germination were observed, at which the seeds behaved as neutral photoblastic; there was no germination at 10 or at 45°C.